The theory of laser materials processing : heat and mass transfer in modern technology / John Dowden, Wolfgang Schulz, editors. - Dowden, John Michael; Schulz, W. (Wolfgang), 1958- (Springer series in materials science ;, 2017)
The purpose of this book is to show how general principles afford insight into laser processes. The principles may be from fundamental physical theory or from direct observation, but understanding of the general characteristics of a process is essential.